Business Feasibility Study Analysis in Islamic Economics Review (Study of Marketing and Operational Management Aspects in the Mischa Crackers Industry in Kampung Melayu District) - Sela Febriani; Nurul Hak; Rizky Hariyadi; Suherman (Sharia Economic and Management Business Journal (SEMBJ), 2023)
The purpose of this writing is to find out how the feasibility of business in the Mischa cracker industry in Islamic economic review in the aspects of marketing and operational management. To find out this, researchers used descriptive qualitative methods with data collection techniques and used observation, interview and documentation methods. From the results of research and discussion, it is found that it has met all the criteria for business feasibility in marketing and operational management aspects when viewed based on general economic concepts. When viewed from an Islamic point of view, the marketing aspect still has business information defects, but the business can be said to be Islamically feasible when viewed from operational management.